Pengaruh Ukuran Partikel Simplisia Daun Rhizophora mucronata terhadap Profil FTIR yang Dikombinasi dengan Kemometrik - Lina Permatasari; Neneng Rachmalia Izzatul Mukhlishah; Legis Ocktaviana Saputri; Selvira Anandia Intan Maulidya; Alfini Junaida; Risma Fitriani; Dzakiyyah Sulthanah Ahmad; Nisa Isnaini (Universitas Hamzanwadi, 2026)
Rhizophora mucronata leaves contain various secondary metabolites that contribute to several pharmacological activities. The extraction efficiency and metabolite composition can be influenced by several factors, including the particle size of plant materials. This study aimed to evaluate the effect of particle size of R. mucronata leaves on their secondary metabolite composition using Fourier Transform Infrared (FTIR) spectroscopy combined with chemometric analysis. Dried leaves were ground and sieved into different particle sizes (4000 μm, 2000 μm, 500 μm, 177 μm, and 105 μm) using mesh sizes 5, 10, 35, 80, and 140. Each sample was extracted by ultrasound-assisted extraction (UAE) using 96% ethanol. The chemical profiles of the extracts were analyzed using FTIR spectroscopy. The dominant wavenumbers were further evaluated using Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA). The results showed that smaller particle sizes produced higher extraction yields. FTIR spectra revealed the presence of functional groups including O–H, C=O, C–O, and aromatic groups. Biplot on PCA indicated that O–H and C=O functional groups strongly influenced samples with particle sizes of 500 µm and 105 µm. The score plot classified the five samples into three groups: 105 µm and 500 µm (Group I), 2000 µm and 4000 µm (Group II), and 177 µm (Group III). Meanwhile HCA revealed high similarity (79.49%) between the 105 µm and 500 µm samples, while the sample 4000 µm and 105 µm showed low similarity (24.50%). These findings indicate that particle size significantly influences the composition of extracted secondary metabolites.